FIVE YEAR PROGNOSIS IN PATIENTS WITH CORONARY HEART DISEASE AND COMORBIDITIES: DATA FROM MULTICENTER STUDY IN INGUSHETIA REPUBLIC - P. O. Ugurchieva; R. T. Didigova; Z. O. Ugurchieva; M. N. Mamedov (Российский кардиологический журнал)
Aim. Analysis of the primary endpoints occurence in male and female cohort of coronary heart disease (CHD) patients comorbid with other somatic pathology, during 5 years.Material and methods. To the study, 320 patients included (143 males, 177 females, age 46-72 y. o.) with CHD stable angina I-III functional class, and underwent investigations in the year 2012 in three medical centers in the Republic of Ingushetia. In 2017 patients were invited for second investigation or were contacted by phone. As the primary endpoints the following accounted: revascularization surgery (CBG), endovascular surgery in coronary, carotid, peripheral arteries, diagnosed myocardial infarction, ischemic stroke, diabetes and its complications, fatal outcome from cardiovascular diseases (CVD) and death from other causes.Results. The number of CHD patients with comorbidities was 196, and with no comorbidities — 124. During the follow-up, stroke developed in 17 (5 males, 11 females) patients, myocardial infarction in 37 (20 males, 17 females), diabetes in 38 (15 males, 23 females), fatal CVD outcome in 11 (8 males, 3 females; of those in 5 — acute coronary syndrome, 4 — stroke, 3 — chronic heart failure), and death from other causes in 8 (5 males, 3 females). We also analyzed the development of composite endpoints in CHD patients depending on the presence and absence of comorbidities. Stroke was registered in 13 comorbid patients vs 3 in CHD with no other diseases. Myocardial infarction found in 33 patients with CHD and three comorbidities vs 4 cases in CHD with no comorbidities. Diabetes was found in 32 vs 6 patients, respectively; CVD death in 10 vs 1, resp.; all-cause death in 5 vs 3, resp.Conclusion. Comorbid CHD with 2 and more somatic diseases, during the 5-year period of follow-up, does increase the risk of complications and death from CVD.